Recent developments and future prospects of magnesium–sulfur batteries - Wang, Liping; Riedel, Sibylle; Drews, Janina; Zhao-Karger, Zhirong (Frontiers in Batteries and Electrochemistry, 2024)
Rechargeable magnesium (Mg) batteries are promising candidates for the next generation of energy storage systems due to their potential high-energy density, intrinsic safety features and costeffectiveness. Among the various electrochemical couples, the combination of an Mg anode with a sulfur (S) cathode stands out as an attractive option, as it offers a remarkable theoretical volumetric energy density exceeding 3200 Wh L -1 . However, owing to the unique properties of Mg-ion electrolytes, Mg polysulfides and the surface passivation of Mg metal anodes, the development of Mg-S batteries is facing multiple challenges. In this review, recent advancements in designing efficient electrolytes for Mg-S battery systems are summarized. Apart from electrolytes, we also discuss the progress made in fabricating new S cathode composites, Mg anodes and functional separators, focusing on their roles in addressing the critical issues of the Mg-S systems. Finally, it is worth pointing out that the collaborative research combining experimental investigations and theoretical modelling could provide deeper insights into the mechanisms of Mg-S battery systems and promote their development. Overall, the comprehensive insights about the S-redox reaction, polysulfide shuttle problems and degradation mechanism in Mg-S batteries are discussed, which is of profound importance for creating solutions to enhance the overall performance of Mg-S batteries. This review aims to providing an overview of the current state of the research to stimulate innovative thoughts on the fundamental guidelines for facilitating development of Mg-S batteries.